Quantum Technology: Driving Commercialisation of an Enabling Science III 2023
DOI: 10.1117/12.2645095
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement distribution quantum networking within deployed telecommunications fibre-optic infrastructure

Abstract: Quantum networks have been shown to connect users with full-mesh topologies without trusted nodes. We present advancements on our scalable polarisation entanglement-based quantum network testbed, which has the ability to perform protocols beyond simple quantum key distribution. Our approach utilises wavelength multiplexing, which is ideal for quantum networks across local metropolitan areas due to the ease of connecting additional users to the network without increasing the resource requirements per user. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results of our measurements based on the sample of 206 compensations on a full-mesh four-user network show that it takes 14 min average per link to achieve average polarization visibility of (98.17 ± 0.04)% after compensation. Our previous research [23] showed polarization stability that corresponds to the average standard deviation of QBER of 0.6% after compensation with manual controllers over a period of 10.8 days. This period includes cooling cycles of superconducting detectors every 24 hours over which the network was not running but it fully recovered its functionality after cycling.…”
Section: Canonical Methods Using An Auxiliary Laser For Polarization ...mentioning
confidence: 91%
“…The results of our measurements based on the sample of 206 compensations on a full-mesh four-user network show that it takes 14 min average per link to achieve average polarization visibility of (98.17 ± 0.04)% after compensation. Our previous research [23] showed polarization stability that corresponds to the average standard deviation of QBER of 0.6% after compensation with manual controllers over a period of 10.8 days. This period includes cooling cycles of superconducting detectors every 24 hours over which the network was not running but it fully recovered its functionality after cycling.…”
Section: Canonical Methods Using An Auxiliary Laser For Polarization ...mentioning
confidence: 91%